Thermodynamic Characterization of Polyetherimide/Single-Walled Carbon Nanotube Composites - Isik, Birol; Ugraskan, Volkan; Yazici, Ozlem; Cakar, Fatih (OXFORD UNIV PRESS INC, 2024)
The aim of this study is to examine the interactions of composite materials obtained by adding single-walled carbon nanotubes (SWCNT) to polyetherimide (ULTEM) in different weight ratios with various organic solvents, and to evaluate the solubility of composites in these organic solvents. The characterization of prepared composites was performed with SEM analysis. Thermodynamic properties of ULTEM/SWCNT composites were determined by the inverse gas chromatography (IGC) method at 260-285 degrees C in infinite dilution. According to the IGC method, the retention behaviors were examined by passing different organic solvent vapors over the composites used as stationary phase, and retention diagrams were drawn using the obtained retention data. Thermodynamic parameters including Flory-Huggins interaction parameters (chi(infinity)(12)) , equation of state interaction parameters (chi(& lowast;)(12)), weight fraction activity coefficients in infinite dilution (omega(infinity)(1)), effective exchange energy parameters (chi(eff)), partial molar sorption enthalpies (delta(sic)(S)(1)), partial molar dissolution enthalpies in infinite dilution (delta(sic)(infinity)(1)) and molar evaporation enthalpies (delta(sic)(v)) were calculated using the linear retention diagrams. According to chi(infinity)(12) ,chi(& lowast;)(12), omega(infinity)(1) and chi(eff) values, organic solvents were found to be poor solvents for composites at all temperatures. Besides, the solubility parameters of composites were determined by IGC method at infinite dilution.
Keywords: INVERSE GAS-CHROMATOGRAPHY; LIQUID-CRYSTALLINE; INFINITE DILUTION; NANOCOMPOSITES; SOLUTES; Biochemistry & Molecular Biology; Chemistry